IMPACT OF AIR POLLUTION ON RESPIRATORY HEALTH IN URBAN AREAS OF CHILE - Matías Orallama Gajardo (CV. Fahr Publishing, 2024)
This study examines the impact of air pollution on respiratory health in urban areas of Santiago, Chile, focusing on the correlation between exposure to particulate matter (PM2.5, PM10), nitrogen dioxide (NO2), and ozone (O3) and the prevalence of respiratory conditions such as asthma, chronic obstructive pulmonary disease (COPD), and other symptoms. Using a mixed-methods approach, data were collected through structured surveys, air quality monitoring, and qualitative interviews with residents from both high- and low-pollution areas of Santiago. The results revealed a significantly higher prevalence of respiratory conditions in high-pollution areas, with asthma being reported by 45% of residents compared to 25% in low-pollution areas. The incidence of COPD was also higher in areas with more pollution, with 18% of residents suffering from the condition compared to 9% in less polluted areas. The air quality data showed that PM2.5 levels in high-pollution areas exceeded recommended limits, correlating with the reported health issues. Interviews further highlighted the discomfort and anxiety associated with air pollution exposure, with many participants reporting increased reliance on medication. Socioeconomic factors also played a significant role in health outcomes, as individuals in lower-income areas had limited access to protective measures such as air purifiers and medical treatments. The findings emphasize the need for stronger public health interventions and urban planning efforts aimed at reducing air pollution and mitigating its adverse effects on respiratory health, especially among vulnerable populations. This research provides valuable insights for policymakers working to address air quality and health disparities in rapidly urbanizing cities.